Innovations as Drivers of Stable Growth of the Kazakh Economy through State Policy in Area of Eco-innovations Implementation - Bekniyazova, Dana Saylauovna; Akishev, Arman; Kaliyev, Ildar; Shamshudinova, Gulnara Turganovna; Altybassarova, Meiramgul Armiyanovna (International Journal of Energy Economics and Policy, 2016)
One of the main tasks of the state when achieving the stable economy growth is to stimulate a growth of the energy efficiency in energy intensive sectors of economy and to form the efficient regulatory basis to decrease the energy ratio. Therefore, the main task of the state power is to provide efficient, reliable, and ecologically responsible supply of energy resources. Thus, in 2013 the Government of the Republicof Kazakhstandeveloped and adopted the Concept on Transferring to “Green Economy”. Its basic goal is to provide reliable, adequate and accessible energy resources for substantial social, economic, and ecologically stable growth of the country. The research conducted within this article allows to make the conclusion that at the present time the Republic of Kazakhstan has a very low level of energy efficiency. In spite of considerable positive changes in the development of innovations, in accordance with the classification of the 2015 Global Innovation Index, Kazakhstanis ranged as an inefficient innovator with a low level of investments in research and development works and low demand for eco-innovations. Keywords: eco-innovations, green technologies, green power industry, national innovational strategy, energy efficiency, energy ratio, resources of renewable energy sector (RRES). JEL Classifications: N55, O13, P28